Predominance of STEMI and severity of coronary artery disease in a cohort of patients hospitalized with acute coronary syndrome: a report from ABC Medical School - Bacci,Marcelo Rodrigues (2015)
Summary Introduction: acute coronary syndromes (ACS) represent a widely prevalent health issue with high mortality in Brazil and worldwide. The severity of ACS is not known in patients in the city of São Bernardo do Campo a municipality contiguous and adjacent to the city of São Paulo. Objectives: to study the profile of coronary disease in patients hospitalized with ACS who underwent coronary angiography in the emergency room between 2012 and 2013. Methods: this is an observational study that included consecutive patients with ACS admitted to the emergency room of a hospital. Data collection was performed using medical records with the following variables: sex, age, risk factors for cardiovascular disease, coronary angiography. Results: the sample in this period included 131 patients, of which 64.8% were men. The most prevalent diagnosis was ST-elevation myocardial infarction (STEMI) (57.2%) followed by non-ST-elevation myocardial infarction (NSTEMI) (22.1%) and unstable angina (UA) (20.6%). There were no significant differences in the epidemiology and risk factors between the diagnoses, except that heart failure was more prevalent in patients with UA. Discussion: there were no differences between groups regarding the coronaries involved; however, STEMI patients showed similar numbers of multi- and singlevessel lesions, NSTEMI patients showed more multivessel lesions, and UA patients showed more multivessel lesions or lesion-free arteries. Although multivessel lesions were prevalent in all groups, STEMI patients showed a significantly higher number of single-vessel lesions compared with the other acute coronary syndromes. Conclusion: the study demonstrated a predominance of STEMI in the studied population, which differs from the usual results in ACS.